ANALISIS RISK MANAGEMENT DISCLOSURE : Pada BankUmum Konvensional Yang Terdaftar Di BursaEfek Indonesia - Gitna Revania Hunah (2021)
This research is using quantitative study aimed to see wheter there the effect of firm size, leverage, and profitability on risk management disclosure. The population used in this study is the Conventional Commercial Bank, which numbered 41 companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. By using saturation sampling method and using all banking companies with research period of four years to obtain 123 sample units. This research was conducted using a panel data regression to test the hypothesis and assisted by the program E-views 10, with a significance rate of 5% (0,05). The results obtained by this research are (1) firm size significantly influent on risk management disclosure, (2) There is no significant effect found between leverage on risk management disclosure, (3) There is no significant effect found between profitability on risk management disclosure.